Chemical composition and antibacterial activity against staphylococcus aureus ATCC 25923 of the essential oils from Baccharis spartioides ("Pichana") extracted by steam distillation - Manso, Victoria (2020)
Baccharis spartioides is a plant aromatic member of the Asteraceae family. Its branches are strongly scent because of the presence of a wide variety of volatile compounds that have demonstrated antimicrobial activity. The present work aims to determine essential oil composition of B. spartioides (BsEO) and assess the antimicrobial activity against Staphylococcus aureus. BsEO was obtain by steam distillation, and its composition was determine by GC-MS. The antimicrobial activity was evaluated by a disc diffusion test in which the diameter of the clear zone around the disc was measured and expressed in millimeters. It was assess the antimicrobial activity by increasing volumes of BsEO impregnated on disc using 6 L of pure limonene (97%) and Amikasin (30 g) as discs control. It was considered diameters >20 mm by significant inhibitory effect. The majors constituents of BsEO were limonene (44%), sphatulenol (12%) and caryophyllene oxide (8%). Since limonene is BsEO major constituent, we considered this component as responsible for antimicrobial activity. Thus, the calibration curve of L of limonene vs diameter was made and it was determined that 6 L of BsEO was the minimal volume for significant inhibitory effects. Major antimicrobial activity was expressed in discs impregnate with 5, 6, 7, and 8 L of BsEO, which diameters was inferior to 20 mm. Results indicate BsEO present low antimicrobial activity (<20 mm) a but inhibition diameters founded (10-15 mm) could correspond to bacteriostatic activity.